Komentar editor: Posisi teori dalam artikel penelitian - Hendryadi Hendryadi (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2021)
The role of theory, significantly in journal articles, is one of the editors' concerns when evaluating content. Although many writers are very familiar with the terms "theoretical basis," "theoretical framework," and "theoretical background," which are written interchangeably in various scientific journal articles, most writers still do not understand what their functions and uses are. This conclusion is based on the evaluation results of the editorial team on articles that have entered the editorial desk over the last two years, giving rise to an idea for us to explain how the role and function of theory in scientific articles, from the perspective of the SERAMBI editorial team, based on various considerations and popular references.